Bangladesh Tertiary Education : SABER Country Report 2017 - World Bank Group (World Bank, Washington, DC, 2017)
SABER-Tertiary Education is a diagnostic tool to assess how education systems perform and to identify priorities for reforms at the national level. It is part of the World Bank’s Systems Approach for Better Education Results (SABER), which aims to benchmark education systems at the country level. Bangladesh faces an optimistic scenario in terms of social and economic development. It is one of the world’s most populous countries with an estimated 160 million people.This report proceeds as follows. First, the authors describe the context of the tertiary education system in Bangladesh. The authors then proceed with scoring the six policy dimensions with descriptions followed by a conclusion with a few general observations about tertiary education in Bangladesh.